2017
DOI: 10.1007/978-3-319-55330-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Bioenergetics During Ischemia and Reperfusion

Abstract: During ischemia and reperfusion (I/R) mitochondria suffer a deficiency to supply the cardiomyocyte with chemical energy, but also contribute to the cytosolic ionic alterations especially of Ca. Their free calcium concentration ([Ca]m) mainly depends on mitochondrial entrance through the uniporter (UCam) and extrusion in exchange with Na (mNCX) driven by the electrochemical gradient (ΔΨm). Cardiac energetic is frequently estimated by the oxygen consumption, which determines metabolism coupled to ATP production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 91 publications
0
32
0
Order By: Relevance
“…Given the potential of Rg1 to abolish the no reflow in the reperfusion phase, this mechanism is certainly a contributor in this respect, although the cause and effect relation between its effect on improving MBF and energy metabolism remains an open question. Another mechanism is to modulate the activity and/or expression of mitochondria respiratory chain Complexes, the machinery for synthesis of ATP (Consolini et al, 2017 ). The results from the present study demonstrated that this mechanism contributes indeed to the energy improving role of Rg1 in myocardial I/R injury, as evidenced by the increase in the activity of these Complexes by Rg1 pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential of Rg1 to abolish the no reflow in the reperfusion phase, this mechanism is certainly a contributor in this respect, although the cause and effect relation between its effect on improving MBF and energy metabolism remains an open question. Another mechanism is to modulate the activity and/or expression of mitochondria respiratory chain Complexes, the machinery for synthesis of ATP (Consolini et al, 2017 ). The results from the present study demonstrated that this mechanism contributes indeed to the energy improving role of Rg1 in myocardial I/R injury, as evidenced by the increase in the activity of these Complexes by Rg1 pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, very little is known about how environmental stresses are sensed and encoded into epigenetic changes the quantification of characterization of morphological changes using microscopy imaging techniques (Coggan, 1995;Hughes et al, 2015). Many of these indexes have been associated with aging and increased risk of chronic conditions (Consolini et al, 2017;Gonzalez-Freire et al, 2018). Several assays are available for measuring ROS generation, antioxidant defense, and oxidative damage to macromolecules in blood, cells, and tissues (Dikalov & Harrison, 2014;Starkov, 2010).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…In humans, mitochondrial metabolic function is often studied in vitro in skeletal muscle by respirometry in permeabilized muscle fibers obtained through biopsies, as well as in vivo by phosphorous magnetic resonance spectroscopy (P 31 MRS) (Lanza & Nair, ). Using both methods, it has been demonstrated that the degree of oxidative phosphorylation declines with aging in humans in the heart, skeletal muscle, and other tissues (Coen et al, ; Consolini, Ragone, Bonazzola, & Colareda, ; Fabbri et al, ; Gonzalez‐Freire et al, ; Holloway et al, ). Reduced mitochondrial function is associated with mobility decline in older persons, while the effect is mediated by a reduction of muscle strength (Zane et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the lack of ATP production is the basis for myocardial I/R injury, and the sharp increase of reactive oxygen species (ROS) along with the intracellular calcium overload are the central parts of I/R injury. In addition, I/R injury involves in many other factors such as apoptosis, mitochondrial permeability transition, in ammation, and so on [6][7][8].…”
Section: Introductionmentioning
confidence: 99%